(untitled) (Research, Society and Development, 2022)
Patients with RA have a wide variety of TMJ changes. Such changes range from various cortical and small structures and articular eminence, globular and articular eminence, destructive in physiology, increased joint mobility and ankylosis. Temporomandibular disorders (TMDs) did not do well in rheumatized patients with patient involvement and were not diagnosed in their clinic yet did not do well in the literature. Given the above, the present study aimed to evaluate the involvement of the temporomandibular joint in patients with rheumatoid arthritis. Two controlled patients with medical follow-up from Amazonas Adriano Jorge who underwent a hospital follow-up and clinical examination of the follow-up state2 of the State University (UEA) were investigated. The findings of female patients represent the largest number of cases of TMJ dysfunction in RA-related data. The patient’s age of the disease contributes and the time of progression of the symptoms presented. As more changes in TMJ were in mandibular fossa, presence of osteophyte changes and conditional planning.